2008
DOI: 10.1074/mcp.m800160-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Interactome of Helicobacter pylori Urease Revealed by Tandem Affinity Purification

Abstract: In the human gastric bacterium Helicobacter pylori, two metalloenzymes, hydrogenase and urease, are essential for in vivo colonization, the latter being a major virulence factor. The UreA and UreB structural subunits of urease and UreG, one of the accessory proteins for Ni 2؉ incorporation into apourease, were taken as baits for tandem affinity purification. The method allows the purification of protein complexes under native conditions and physiological expression levels of the bait protein. Protein-protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
114
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 76 publications
5
114
0
Order By: Relevance
“…Stingl et al (67) already observed some unexpected proteins in their complexes, for example, cell division factors (MinD, Tig, FtsA, Fig. 6).…”
Section: The Helicobacter Pylori Interactomementioning
confidence: 99%
See 1 more Smart Citation
“…Stingl et al (67) already observed some unexpected proteins in their complexes, for example, cell division factors (MinD, Tig, FtsA, Fig. 6).…”
Section: The Helicobacter Pylori Interactomementioning
confidence: 99%
“…Stingl and colleagues have isolated eight protein complexes associated with urease components (67). Based on the known PPIs we investigated which binary interactions explain the the complexesЈ topology.…”
Section: The Helicobacter Pylori Interactomementioning
confidence: 99%
“…For example, an interaction between H. pylori UreE and HypA, the latter protein being a component of the [NiFe] hydrogenase maturation pathway, has been shown to be necessary for urease maturation (9). Similarly, H. pylori UreG can interact with another hydrogenase maturation protein, HypB (6).…”
mentioning
confidence: 99%
“…While most bacterial ureases are composed of three different subunits that form a (UreABC) 3 ions into urease requires a series of maturation proteins that have been best-studied in Klebsiella aerogenes, including UreD (UreH in H. pylori), UreE, UreF, and UreG (2). Interactions between the urease apoprotein subunits and maturation proteins, as well as interactions among the maturation proteins themselves, have been identified by various approaches in K. aerogenes (reviewed in ref 1), Proteus mirabilis (3), and H. pylori (4)(5)(6). Although the specific molecular roles of each of the accessory proteins in metal center maturation and the requirements for protein-protein interactions are not clear, the overall conclusion from studies of K. aerogenes is that UreD, UreF, and UreG form a complex with the urease apoprotein while UreE functions in Ni 2þ delivery.…”
mentioning
confidence: 99%
“…The basic building blocks of proteomic interaction networks are binary protein-protein interactions (PPi). Proteome-scale PPi studies were described for E. coli (6 -11), and a few gram-negative pathogens (12)(13)(14)(15), although only limited data for Y. pestis and other highly virulent bacteria currently exists.…”
mentioning
confidence: 99%